Cracking Failure Analysis on 316L Stainless Steel Elbow. (November 2020) - Hu, Jiakun; Ren, Facai; Fu, Chunxia
Abstract: The 316L stainless steel elbow used in the pulse soot blower cracked during service, and the cracking occurred at the maximum bending radius of the elbow. There is no obvious plastic deformation at crack and there is much rust deposit on the inner elbow wall of cracked elbow. In order to avoid similar accidents, the methods such as chemical composition analysis, microstructure analysis and crack pattern scanning are adopted to analyze crack reason. The results show that stress corrosion is the main reason to cause crack of 316L stainless steel elbow.